Humoral and Cellular Response Following Vaccination With the BNT162b2 mRNA COVID-19 Vaccine in Patients Affected by Primary Immunodeficiencies - Amodio, Donato; Ruggiero, Alessandra; Sgrulletti, Mayla; Pighi, Chiara; Cotugno, Nicola; Medri, Chiara; Morrocchi, Elena; Colagrossi, Luna; Russo, Cristina; Zaffina, Salvatore; Di Matteo, Gigliola; Cifaldi, Cristina; et al. (Frontiers in Immunology, 2021)
Mass SARS-Cov-2 vaccination campaign represents the only strategy to defeat the global pandemic we are facing. Immunocompromised patients represent a vulnerable population at high risk of developing severe COVID-19 thus should be prioritised in the vaccination programs and in the study of the vaccine efficacy. Nevertheless, most data on efficacy and safety of the available vaccines derive from trials conducted on healthy individuals; hence, studies on immunogenicity of SARS-CoV2 vaccines in such populations are deeply needed. Here we perform an observational longitudinal study analyzing the humoral and cellular response following BNT162b2 mRNA COVID-19 Vaccine in a cohort of patients affected by Inborn errors of immunity (IEI) compared to Healthy controls (HC). We show that both EIE and HC groups experienced a significant increase in anti SARS-CoV-2 Abs one week after the second scheduled dose as well as an overall statistically significant expansion of the Ag-specific CD4+CD40L+ T cells in both HC and IEI. Five IEI patients did not develop any specific CD4+CD40L+ T cellular response with one of these patients unable to mount also any humoral response. This data raises immunologic concerns about using Ab response as a sole metric of protective immunity following vaccination for SARS-CoV-2. Taken together, these findings suggest that evaluation of vaccine induced immunity in this subpopulation should also include quantification of Ag specific T cells.